2010
DOI: 10.1111/j.1365-3083.2010.02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Expression, Purification and Immunological Characterization of Three Low-Molecular Weight Proteins Encoded by Genes in Genomic Regions of Difference ofMycobacterium Tuberculosis

Abstract: The aim of this study was to clone, express and purify three major antigenic proteins, i.e. Rv3874, Rv3875 and Rv3619c, encoded by genes located in regions of difference of Mycobacterium tuberculosis and characterize them for immunogenicity in rabbits. The respective genes were amplified using gene‐specific primers and genomic DNA of M. tuberculosis by polymerase chain reaction. The amplified DNA were cloned into pGEM‐T Easy and subcloned into pGES‐TH‐1 vector for high‐level expression in Escherichia coli and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…testing of sera with individual peptides of each protein demonstrated that rabbit antibodies recognized several linear epitopes that were scattered throughout the sequence of each protein (Hanif et al, 2010a). Interestingly, previous studies using pools of synthetic peptides have shown that all of these proteins (Rv3874, Rv3875 and Rv3619c) are major T cell antigens in humans, and the linear T cell epitopes were scattered throughout the sequence of these proteins Mustafa et al 2000Mustafa et al , 2008.…”
Section: Molecular Cloning Expression Purification and Immunologicamentioning
confidence: 99%
See 4 more Smart Citations
“…testing of sera with individual peptides of each protein demonstrated that rabbit antibodies recognized several linear epitopes that were scattered throughout the sequence of each protein (Hanif et al, 2010a). Interestingly, previous studies using pools of synthetic peptides have shown that all of these proteins (Rv3874, Rv3875 and Rv3619c) are major T cell antigens in humans, and the linear T cell epitopes were scattered throughout the sequence of these proteins Mustafa et al 2000Mustafa et al , 2008.…”
Section: Molecular Cloning Expression Purification and Immunologicamentioning
confidence: 99%
“…The results showed that the recombinant Rv3874 and Rv3875 proteins were contaminated with another protein of nearly 70 kDa, whereas Rv3619c protein was nearly homogeneous (more than 95% pure). The partially purified Rv3874 and Rv3875 proteins were further purified on Ni-NTA agarose affinity matrix, and the analysis of eluted fractions showed the presence of a single sharp band in SDS-PAGE gels, which suggested that Rv3874 and Rv3875 preparations became free of the 70-kDa contaminant and were nearly homogeneous (more than 95% pure) (Hanif et al, 2010a). These results further strengthen the suggestion that pGES-TH-1 is useful for high level expression and efficient purification of recombinant mycobacterial proteins (Ahmed et al, 2003;.…”
Section: Molecular Cloning Expression Purification and Immunologicamentioning
confidence: 99%
See 3 more Smart Citations